TRANSFORMASI BUDAYA IKAT NAMO DI KAMPUNG HARAPAN KECAMATAN SUNGAI APIT KABUPATEN SIAK - Loli Ana Picha; Titi Maemunaty; Wilson ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem formulation in this research is how is the transformationof ikat namo culture in Harapan Village, Sungai Apit Subdistrict, Siak District? Thepurpose of this research is to know the transformation of namo bunch culture inHarapan Village, Sungai Apit Subdistrict, Siak District. The type of this research isdescriptive naturalistic with qualitative approach. The subject of this research as manyas 6 people, the technique of taking the data source is by snowball sampling. Theinstrument of this study used participant observation, interview and documentation. Theresults of the analysis carried out then can in the conclusion of the process oftransformation of namo culture is through three stages, namely the preliminary stage,the stage of implementation and the final stage.Keywords : Transformation, Culture, Ikat Namo.